PROFESIONALISME GURU DALAM MENGEMBANGKAN MODEL PEMBELAJARAN BERBASIS TEKNOLOGI - Munawir; Wahyuni Ramadhani; Zahra Diyana Adibah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze teacher professionalism in the digital era at Madrasah Ibtidaiyah (MI). The rapid development of technology requires teachers to adapt to digital-based learning and improve their competencies. This research employs a qualitative approach using a literature study method by analyzing various relevant scientific sources such as journals, books, and research articles. The findings indicate that teacher professionalism in the digital era is reflected in the mastery of digital literacy, the ability to integrate technology into learning, and the development of innovative and adaptive teaching strategies. However, several challenges are still faced, including limited technological skills, inadequate infrastructure, and resistance to change. Therefore, continuous training, institutional support, and the development of digital competencies are essential to enhance teacher professionalism. This study concludes that improving teacher professionalism in the digital era is a crucial factor in creating effective and relevant learning processes.